Hepatic Fat—Genetic Risk Score Predicts Hepatocellular Carcinoma in Patients With Cirrhotic HCV Treated With DAAs. Issue 6 (20th November 2020) - Degasperi, Elisabetta; Galmozzi, Enrico; Pelusi, Serena; D'Ambrosio, Roberta; Soffredini, Roberta; Borghi, Marta; Perbellini, Riccardo; Facchetti, Floriana; Iavarone, Massimo; Sangiovanni, Angelo; Valenti, Luca; Lampertico, Pietro
Abstract : Background and Aims: Genetic factors and steatosis predispose to hepatocellular carcinoma (HCC) in patients with chronic hepatitis C virus; however, their impact in patients with cirrhosis cured by direct‐acting antivirals (DAAs) is still undefined. We assessed the association between a genetic risk score (GRS) of hepatic fat accumulation, combining variants in PNPLA3 (patatin‐like phospholipase domain containing 3), MBOAT7 (membrane bound O‐acyltransferase domain containing 7), TM6SF2 (transmembrane 6 superfamily member 2), GCKR (glucokinase regulator), and HCC in patients treated with DAAs. Approach and Results: We considered 509 consecutive patients with HCV cirrhosis (defined histologically or when liver stiffness ≥12 kPa) treated with DAAs. HCC was diagnosed according to international recommendations. GRS was calculated from the weighted impact of single variants on hepatic fat content quantified by H 1 spectrometry in the general population (Dallas Heart Study). During a median follow‐up of 43 (3‐57) months after DAA start, 36 of 452 (8%) patients developed de novo HCC, 4‐year cumulative probability being 9% (95% confidence interval 7%‐12%). Male sex (hazard ratio [HR] 2.54, P  = 0.02), diabetes (HR 2.39, P  = 0.01), albumin (HR 0.35, P  = 0.001), and GRS score >0.597 (HR 2.30, P  = 0.04) were independent predictors of de novo HCC. In contrast, single genetic risk variants were not useful in stratifying HCC risk. The proportion of patients who developed HCC according to the combination of the independent risk factors ranged from 11% to 67%. HCC recurred in 28 of 57 (49%) patients with previous history; diabetes and ethnicity were the only independent predictors of HCC recurrence. Conclusions: In a large cohort of DAA‐treated patients with cirrhotic HCV, GRS was associated with de novo HCC independently of classical risk factors, including liver disease severity. These data suggest that hepatic fat (i.e., lipotoxicity) promotes HCC in this setting and may represent a target for chemoprevention. Combination of clinical and genetic predictors may improve HCC risk stratification.